Reflecting on the ethics of moblile eye-tracking in a mixed mehtods research design - Kaufmann, Katja; Rauhala, Marjo; Gudowsky, Niklas; Rutzinger, Martin; Bork-Hüffer, Tabea (AoIR2020, 2020)
AoIR and the Journal of Information, Communication and Ethics in Society (JICES) share common interests in critical reflection on the ethical and social dimensions of the internet and internet-facilitated communication, and have begun a collaboration aimed at collecting ethically-focused AoIR conference submissions for presentation and critique at AoIR, with a view towards subsequent publication in a special issue of JICES. This panel collects three papers that address these shared interests as specifically focused on research ethics. Paper 1, Integrating Mobile Eye-Tracking in a Mixed Methods Research Design: Ethical Standards and Practical Requirements, addresses the social and data ethical dimensions of the increasing use of Augmented Reality (AR) technologies in public spaces. Paper 2, The complex balancing act of researchers’ ethical and emotional capacities and responsibilities, takes up these issues from the first-hand experience of a researcher-participant who, as a bereaved parent, was requested to research a closed community for bereaved parents on Facebook. The wide range of ethical challenges here includes informed consent as distinctively difficult in these contexts. Paper 3, Digital Ethics and the Situationist Challenge to Virtue Ethics, evaluates recent applications of virtue ethics in digital media, arguing instead for a pragmatist, situation-based approach. These three papers thus expand AoIR’s signature focus on Internet Research Ethics through two empirically-oriented papers on research ethics/methods in two specific contexts, complimented by a more theoretical exploration of virtue ethics and pragmatism – and thereby dovetail with JICES’ interests in the ethics and social dimensions of ICTS
Gesehen am 08.05.2025
Teil 1 des Beitrags "Theoretical and practical research ethics: three cases"